2006
DOI: 10.1002/chem.200600442
|View full text |Cite
|
Sign up to set email alerts
|

Designed Boronate Ligands for Glucose‐Selective Holographic Sensors

Abstract: In this study, 2-acrylamidophenylboronate (2-APB) was synthesised and its ability to bind with glucose was investigated both in solution and when integrated into a holographic sensor. Multiple forms of 2-APB, resulting from the neighbouring effect of the amido group with the boronic acid through an intramolecular B--O-coordinated interaction, were shown to exist in solution by using multinuclear NMR spectrometry. It was found that 2-APB predominantly adopts a zwitterionic tetrahedral form at physiological pH v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 30 publications
3
104
0
Order By: Relevance
“…[4] At pH 7.4 the three boronate receptors have been shown to adopt different conformations at the boron centre, [14,24] 3-and 4-APB are predominantly trigonal whereas 2-APB adopts a zwitterionic tetrahedral form. Previous studies have shown that 11 B NMR spectroscopy is a suitable analytical tool for the determination of boronate species, [20,23] and more information concerning the identity of boronate compounds can be obtained by employing this technique, rather than the traditional solution titration methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] At pH 7.4 the three boronate receptors have been shown to adopt different conformations at the boron centre, [14,24] 3-and 4-APB are predominantly trigonal whereas 2-APB adopts a zwitterionic tetrahedral form. Previous studies have shown that 11 B NMR spectroscopy is a suitable analytical tool for the determination of boronate species, [20,23] and more information concerning the identity of boronate compounds can be obtained by employing this technique, rather than the traditional solution titration methods.…”
Section: Resultsmentioning
confidence: 99%
“…A plausible explanation is that in aqueous conditions 2-APB may self-associate to form a trimer that is dissociated on heating to 50 8C, releasing the hydroxyl groups that are then free to react with glucose (Scheme 1). It has also been observed [24] that there are very strong hydrogen bonds between the OH www.chemeurj.org groups of 2-APB, which may partly explain why 2-APB binds only weakly to glucose relative to the "trimer." However, further experimental studies are necessary to confirm which of these hypotheses is most probable.…”
Section: Full Papermentioning
confidence: 92%
“…, (3-acrylamidopropyl)trimethylammonium) with PBA derivatives. [35] Alternatively, PBA derivatives such as 2-acrylamido-5-fluorophenylboronic acid, [8] 2-(acrylamido)phenylboronate, [36] 4-vinylphenylboronic acid (4-VPBA), [37] or their copolymerized combinations [38] can be used to improve the selectivity of the hydrogel fiber sensors to glucose. Electron-withdrawing substituents may increase the sensor response by decreasing the p K a of PBA.…”
Section: Hydrogel Optical Fiber Sensorsmentioning
confidence: 99%
“…Boronic acids display differing binding affinities, independent of size/ charge ratios and for this quality boronic acid-functionalised gels have long since been utilised as a stationary phase for the analysis and separation of mono-, oligosaccharides and oligonucleosides by column chromatography [16]. Since boronic acids have been incorporated into hydrogels as sensors [17][18][19][20] they were the obvious choice of saccharide receptor for incorporation into electrophoresis gels. Electrophoresis gels are commonly a hydrogel assembled by copolymerising acrylamide (compound 1, Fig.…”
Section: Resultsmentioning
confidence: 99%